THE ROLE OF GAMIFICATION IN TEACHING ENGLISH - Iminohunova Munisabonu Akromjon qizi; Sobirova Feruza Islomjon qizi (Web of Journals Publishing, 2025)
This study explores the role of gamification in teaching English and examines how game-based elements can enhance learners’ motivation, engagement, and language proficiency. Drawing on recent research and classroom practices, the paper analyzes key gamification components such as points, badges, levels, challenges, and immediate feedback. The findings suggest that integrating these elements into English lessons encourages active participation, supports sustained attention, and promotes autonomous learning. Moreover, gamification helps create a positive learning environment where learners feel safe to experiment, make mistakes, and improve through repetition. However, the study also highlights potential limitations, including the risk of over-competition and the need for thoughtful instructional design. Overall, the research concludes that when applied effectively, gamification can significantly enrich English language teaching and contribute to more meaningful learning outcomes.
Keywords: Gamification, language learning, English teaching, student motivation, engagement, interactive learning, digital tools, game-based activities, rewards and badges, learner autonomy, classroom participation, educational technology, learning outcomes, motivation strategies, cognitive development, feedback system, points and levels, competition and collaboration, playful learning, task-based learning, mobile learning apps, virtual learning, and innovation in teaching.